2015
DOI: 10.1186/s12889-015-1990-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with uptake of influenza vaccine in people aged 50 to 64 years in Hong Kong: a case–control study

Abstract: BackgroundIn Hong Kong, people aged 50–64 years were added as a recommended priority group (recommended group) for influenza vaccination by the Department of Health (DH) starting from 2011/12 onwards. The coverage rate of influenza vaccination for this age group was suboptimal at 8.5 % in 2012/13. This study investigates the factors associated with the uptake of influenza vaccination among adults in Hong Kong aged 50–64 years.MethodsA case–control study was conducted in communities by street intercept intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
(31 reference statements)
2
16
0
Order By: Relevance
“…Yeung et al showed that the majority of the cases (80.8%) were not aware that they were recommended the influenza vaccine and among the controls (71%), a high percentage of participants deemed vaccination to be unnecessary. Similar to our study, the authors mentioned that this finding showed a failure in communicating the importance of the vaccination to this age group (16). Sevin et al reported ethnic disparities in the knowledge of the influenza vaccine indication, including concern for getting sick from the following treatment (11).…”
Section: Discussionsupporting
confidence: 82%
“…Yeung et al showed that the majority of the cases (80.8%) were not aware that they were recommended the influenza vaccine and among the controls (71%), a high percentage of participants deemed vaccination to be unnecessary. Similar to our study, the authors mentioned that this finding showed a failure in communicating the importance of the vaccination to this age group (16). Sevin et al reported ethnic disparities in the knowledge of the influenza vaccine indication, including concern for getting sick from the following treatment (11).…”
Section: Discussionsupporting
confidence: 82%
“…Matsui et al note that “subjects described these barriers/inconveniences as means of transportation to a clinic, physical disability, and the expense of vaccination per se” [ 99 ]. Concrete financial expenses were reported as a barrier for HCPs (9/117 [ 91 , 112 , 160 , 215 , 273 , 285 , 343 , 394 , 395 ]), children (1/18 [ 205 ]) and the general public (7/191 [ 111 , 181 , 224 , 254 , 340 , 396 , 397 ]). For example, Kelly et al found that among Australian students who were eligible for government-funded vaccines, the likelihood of getting the vaccine was 7 times higher than for individuals who were ineligible for funding [ 395 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of influenza vaccination increased with age as in the previous studies ( 6 7 8 19 ), which is partly because adults aged 65 and over can receive free influenza vaccination through national immunization program for elderly, and partly because they have more utilization for medical services. The vaccination coverage rate is price sensitive and free or reimbursed vaccination has been reported as one of the strongest incentives to increase the vaccination of the young adults in Hong Kong ( 20 ). A study for influenza vaccination of cancer survivors also revealed that younger population had significantly lower vaccination coverage than elderly patients who had greater accessibility to vaccination by no cost ( 21 ).…”
Section: Discussionmentioning
confidence: 99%